RISK FACTORS AND FREQUENCY OF METABOLIC SYNDROME AMONG ADULTS - KHAN, TZ; GHUMRO, S; JALAL, A; MAQSOOD, M; KOUSAR , A; HAQ, TU; KHAN, A; GHAFOOR, K (Biological and Clinical Sciences Research Journal, 2024)
Non-communicable diseases (NCDs) pose a significant public health challenge in developing nations, accounting for the most critical mortality rates and illness burden globally. Approximately 74% of annual worldwide deaths are attributed to non-communicable diseases (NCDs), with 77% of these fatalities happening in nations with low or middle incomes. The global prevalence of metabolic syndrome is recognized as a significant public health concern due to its correlation with an increased risk of developing diabetes and cardiovascular issues in individuals of all age groups, including adults, teens, and children. Objective: To determine the risk factors and frequency of metabolic syndrome among adults. Methods: The current study was a sectional study at HMC Hayatabad Peshawar. This study lasted one year, from April 2023 to April 2024. The total sample size was 1000, determined using the WHO sample size calculator. Experts collected anthropometric measurements, including weight and height. A standardized sphygmomanometer was employed to assess blood pressure. Blood samples were obtained from each subject. The data was analyzed using the SPSS version 23 program. Results: This research had a total of 1000 participants. In our study, there were 550 (55%) male participants, and 450 individuals (35%) identified as female. The average (standard deviation) age was 43.05 (11.2) years. Metabolic syndrome was found to be present in 350 (35%) of the participants. In our research, we found that obese individuals had an odds ratio (OR) of 15.01, individuals aged 51 years or older had an OR of 5.91, and overweight participants had an OR of 5.91. These findings indicate that these groups are at a much higher risk of developing metabolic syndrome. Conclusion: Our research findings suggest that metabolic syndrome is quite frequent in our community, with a higher occurrence among females. According to our research, the primary characteristics that significantly impact participation include hyperglycemia, hypertension, abdominal obesity, high levels of triglycerides, and low levels of high-density lipoprotein (HDL).